The Analysis of Phononological Process on the Students' Pronunciation - usman Sidabutar (JETAL: Journal of English Teaching & Applied Linguistic, 2020)
ABSTRACT The objectives of the study are; 1) the phonological process are dominantly used by the student of Batak Tribes on English Pronunciation.2)to find the problem existence of English version different from the Batak version. The researcher wants to reveal the reasons why the phonological problems exist in pronouncing English of the English students of Batak tribes and also to find out what way that the students will use to solve the phonological process problem in pronouncing English. There were 234 incorrect of pronouncing English as affricatives in 30,27 %, fricatives in 50,68% as the dominant problem and the vowel /e/and long vowel occurred in 19,05%. the students were sometimes not difficult to pronounce long vowels. There might be a reluctance of practicing the real pronunciation to EFL. Pedagogically, the students need to get studying much more than and the English Lecturers practice English twister repeatedly by using English Listening and tendency for consonants and vowels practices. Keywords : Batak Tribes; Batak Tribes’ Pronunciation; Phonology of English Consonant and vowels